Surgical or conservative treatment in ARGP syndrome? A systematic review - Bastia, Paolo; Ghirarduzzi, Paolo; Schiavi, Paolo; Donelli, Davide; Pedrazzini, Alessio; Leigheb, Massimiliano; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: The rectus-adductor syndrome is a common cause of groin pain. In literature the adductor longus is reported as the most frequent site of injury so that the syndrome can be fitted into the adductor related groin pain (ARGP) group. The aim of this study was to define what is the best treatment between surgical and conservative in athletes affected by ARGP in terms of healing and return to play (RTP) time. Methods: A systematic review was performed searching for articles describing studies on RTP time for surgical or conservative interventions for ARGP. A qualitative synthesis was performed. Only 10 out 7607 articles were included in this systematic review. An exploratory meta-analysis was carried out. Due to high heterogeneity of the included studies, raw means of surgery and conservative treatment groups were pooled separately. A random effects model was used. Results: The results showed quicker RTP time for surgery when pooled raw means were compared to conservative treatments: 11,23 weeks (CI 95%, 8.18,14.28, p